2006
DOI: 10.1103/physrevlett.97.150601
|View full text |Cite
|
Sign up to set email alerts
|

Sloppy-Model Universality Class and the Vandermonde Matrix

Abstract: In a variety of contexts, physicists study complex, nonlinear models with many unknown or tunable parameters to explain experimental data. We explain why such systems so often are sloppy; the system behavior depends only on a few 'stiff' combinations of the parameters and is unchanged as other 'sloppy' parameter combinations vary by orders of magnitude. We contrast examples of sloppy models (from systems biology, variational quantum Monte Carlo, and common data fitting) with systems which are not sloppy (multi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
173
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(177 citation statements)
references
References 15 publications
3
173
0
Order By: Relevance
“…In general, the presence of many minima could reflect numerical error or a landscape that truly features multiple minima. The first case occurs frequently when the landscape is sloppy [18,51] global minimum is located inside a long narrow and parabolic shaped valley. Sloppiness can imply difficulties in finding the global minimum, because there is a manifold where the cost function is almost flat.…”
Section: Characterization Of the Cost Landscapementioning
confidence: 99%
“…In general, the presence of many minima could reflect numerical error or a landscape that truly features multiple minima. The first case occurs frequently when the landscape is sloppy [18,51] global minimum is located inside a long narrow and parabolic shaped valley. Sloppiness can imply difficulties in finding the global minimum, because there is a manifold where the cost function is almost flat.…”
Section: Characterization Of the Cost Landscapementioning
confidence: 99%
“…in [6,14]. Thus, it could be shown that it is possible by optimal experimental design methods to diminish the sloppiness effect to a minimum.…”
Section: Discussionmentioning
confidence: 99%
“…The same effect has been independently observed in [12,13] for circadian clock systems described by ODEs and it has been * christian.toensing@fdm.uni-freiburg.de termed as rigidity of the mapping from the parameters to the solutions, where it occupies a space of lower dimension. Moreover, the effect has been shown to emerge naturally in special classes of systems [14] and a broad eigenvalue spectrum of the Hessian or its analogs is also observed in systems in a general physical context [15,16]. The impact of the existence of sloppy directions in the parameter space on optimization has been discussed in [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The pathway model here presented belongs to a class of so-called "sloppy" models (30) (see the Appendix), characterized by having a significant number of poorly known parameters with widely varying sensitivities. As an alternative to our approach, one can utilize methods to reduce the dimensionality of parameter space, transforming into a new set of dimensions (reflecting parameter combinations) that are organized by their overall sensitivities (30)(31)(32). In principle, such an approach can help optimize computations in parameter estimation and identify dependencies in parameter variation.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the eigenvalues are more or less uniformly distributed over approximately 6 orders of magnitude (with occasionally a few exceptionally sloppy eigenvectors); this behavior is characteristic of other sloppy systems (30)(31)(32)(33) …”
Section: Derivation Of Kinase Inactivation Inhibitory Mechanismmentioning
confidence: 99%